Diagnosis and management of anaphylaxis - Ellis, Anne K. (2003)
ANAPHYLAXIS IS A SEVERE SYSTEMIC ALLERGIC reaction that is potentially fatal. It requires prompt recognition and immediate management. Anaphylaxis has a rapid onset with multiple organ–system involvement and is mostly caused by specific antigens in sensitized individuals. Reactions typically follow a uniphasic course, however, 20% will be biphasic in nature. The second phase usually occurs after an asymptomatic period of 1–8 hours, but there may be a 24-hour delay. Protracted anaphylaxis may persist beyond 24 hours. Concurrent β-blocker therapy may adversely affect the response to management. Epinephrine is the treatment of choice and should be administered immediately. Secondary measures include circulatory support, H(1) and H(2) antagonists, corticosteroids and, occasionally, bronchodilators. Post-treatment observation of these patients is necessary, and they should remain within ready access of emergency care for the following 48 hours.